The Concept of Phraseology in the Lituanistic Sources of 18th Century - Aleknavičienė, Ona (Vilnius University Open Series, 2018)
[full article and abstract in Lithuanian; abstract in English] This article addresses the problem of the concepts phraseologism and phraseology in modern linguistic literature. It analyses the history of the concepts phraseologism and phraseology in the Lituanistic sources of Prussian Lithuania (Lithuania Minor) of 18th century and strives to justify the need to use these terms in their broad rather than narrow sense. The terms phraseology and phraseologism are not used in any Lituanistic sources of the 18th century. The Latin term idiotismus, used in the early 18th century philological polemic sources, such as Michael Mörlin’s, Johann Schultz’s and Jacob Perkuhn’s works, is not clearly defined. It could be understood either as (1) a peculiar saying or a figurative expression (i.e., a stable word combination or sentence) or (2) a case of common usage, a language norm recognized by society. The Latin terms Idiotismus, Phrase, Phraseologie, used in the German linguistic literature of the 17th–18th centuries, are not clearly defined either. Due to the lack of clear definitions of the concepts phraseologism and phraseology in the Lituanistic sources of the 18th century and in the 18th century German linguistic literature, it would be appropriate to use the terms phraseologism and phraseology in their broad rather than narrow sense, i.e., to regard the stability of not only a word combination but also of a sentence as a distinctive feature of a phraseologism without emphasizing figurativeness or idiomaticity. The suggested definition would be as follows: a phraseologism is a stable word combination or sentence. The researchers of old Lituanistic sources need the broad definition for two more reasons. First, in the old dictionaries, ethnographic works, and collections of small folklore genres, stable word combinations and sayings were recorded without selection; as they were presented together as specific linguistic facts of some regional variety, they should be analysed as wholes. Second, these combinations and sayings should also be taken as wholes in the analysis of the speech community that used them – phraseologisms, in the broad sense, can be treated as (re)constructive instruments of social and cultural identity, i.e., the analysis of phraseologisms could be used to recognize the mechanism defining the boundaries of identity and to reconstruct the content of social and cultural life.